Coordination of hitting movement revealed in baseball tee-batting - Katsumata, H.; Himi, K.; Ino, T.; Ogawa, K.; Matsumoto, T. (Journal of Sports Sciences, 2017)
Baseball batters must react to pitches delivered to different locations within the strike zone by modulating their movements. In tee-batting practice, such batters place a ball on a tee stand at a location, where they intend to hit the ball, assuming a particular pitch`s trajectory. In the present study, we analysed three-dimensional movements in tee-batting to identify characteristics of the batters` intended impact locations across the strike zone, thereby investigating spatiotemporal features of movement modulation. More specifically, 10 experienced baseball batters performed tee-batting at their preferred impact locations at nine different heights and courses within the strike zone. The distribution of impact locations showed regularity, i.e., the location shifted forward for balls placed high and inside, while it shifted backward for balls placed low and outside. Furthermore, trunk and arm movements showed systematic modulation as the impact locations changed. The duration of bat movement was also location dependent, i.e., hitting the inside ball took more time than hitting the outside ball. Our results indicate that even though movements among body segments were properly coordinated to adjust the bat swing for different impact locations, fine timing adjustments were also required to hit the ball at those preferred impact locations and therefore properly react to differences in flight paths.